2016
DOI: 10.1186/s12940-016-0109-0
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of extreme heat on emergency medical service calls in King County, Washington, 2007–2012: relative risk and time series analyses of basic and advanced life support

Abstract: BackgroundExposure to excessive heat kills more people than any other weather-related phenomenon, aggravates chronic diseases, and causes direct heat illness. Strong associations between extreme heat and health have been identified through increased mortality and hospitalizations and there is growing evidence demonstrating increased emergency department visits and demand for emergency medical services (EMS). The purpose of this study is to build on an existing regional assessment of mortality and hospitalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
51
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 36 publications
(75 reference statements)
3
51
1
1
Order By: Relevance
“…These studies have focused on a variety of outcomes impacted by heat, including cardiovascular disease, respiratory diseases, and asthma [25, 2729]. Recent studies utilizing emergency dispatch data demonstrated that morbidity rates are strongly associated with temperature increases [3032]. Among the elderly, emergency department visits and hospitalizations for a variety of health conditions are more frequent during extreme heat events [25, 3335].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have focused on a variety of outcomes impacted by heat, including cardiovascular disease, respiratory diseases, and asthma [25, 2729]. Recent studies utilizing emergency dispatch data demonstrated that morbidity rates are strongly associated with temperature increases [3032]. Among the elderly, emergency department visits and hospitalizations for a variety of health conditions are more frequent during extreme heat events [25, 3335].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies that have analyzed the relationship between extreme heat and morbidity and mortality; nearly all have concluded that extreme heat is associated with increased risk of death, hospitalizations, and other illnesses, especially illnesses related to the cardiovascular and respiratory systems [ 5 , 6 , 7 ]. Furthermore, researchers have observed increased emergency medical service call volumes during heat events [ 8 , 9 , 10 , 11 , 12 , 13 ]. Bassil et al [ 11 ] concluded, on average, there was a 16% increase in heat related illness calls for every one point increase in humidex.…”
Section: Introductionmentioning
confidence: 99%
“…Income level can affect the patient’s health status and ability to treat or manage pre-existing health conditions leaving them more susceptible to heat illness. For example, diabetes has a strong correlation with low income or poverty households [ 40 ] in addition to a strong correlation with extreme heat vulnerability [ 1 , 13 ]. Drug or alcohol use and the ability to seek help is another confounding factor correlated with both low socioeconomic status [ 22 ] and increased risk of an Emergency Medical Service (EMS) call in an extreme heat event [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, when the demand for medical services is growing (Calkins et al, 2016;Eastwood et al, 2015;Veser et al, 2015;Williams, 2015) and the same trend is expected in the future, demand analysis has become an increasingly important area in every organization. On the other hand, due to serious financial difficulties in most of the countries, budgets became even more limited and reduced.…”
Section: Introductionmentioning
confidence: 99%